Analytical psychology and the ghost of Lamarck: did Jung believe in the inheritance of acquired characteristics?. Issue 2 (4th April 2013) - Rensma, Ritske
Abstract Whether Jung was a Lamarckian or not has always been a hotly debated topic, both within the post‐Jungian community and amongst scholars with an interest in Jung in the wider academic community. Yet surprisingly few substantial pieces of work have been dedicated to it and, to my mind, no one has yet managed to do justice to all the subtleties involved. The scholars who have claimed that Jung is a Lamarckian have, for the most part, oversimplified the debate by failing to discuss the passages in which Jung appears to be defending himself against Lamarckism; the scholars who have defended Jung against Lamarckism, however, have as a rule not adequately dealt with the question of whether these passages actually get Jung off the hook. This paper will attempt to correct this imbalance by putting forward four key passages spanning Jung's career that all represent conclusive evidence that Jung was indeed a Lamarckian. After discussing these, it will then deal in detail with the passages in which Jung appears to be defending himself against Lamarckism, making the case that they do not represent a defence against Lamarckism at all and have therefore generally been misinterpreted by many scholars.